Protandrous hermaphroditism in the clown fish Amphiprion percula from Andaman and Nicobar Islands - Madhu, K; Madhu, Rema (Indian Journal of Fisheries, 2011)
<!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> Gonadal sex differetiation through histological analysis and social structure were investigated in anemone fish Amphiprion percula occuring in Andaman and Nicobar islands. Field observation in different locations of Bay island showed that this species is always seen in association with their host sea anemones Heteractis magnifica H. crispa and Stichodactyla gigantea as small social groups that include an adult pair and one to three juveniles (sub adults) and the largest fish is usually the female and the next largest one is the functional male. Considerable size difference consistently appeared between the sexually active female and male, and noticed that a hierarchy exists in which the female is the dominant individual in a social group. Histological examination of gonads indicated that all juveniles start their life as male and subsequently changes into females as they reach larger sizes and mature. Based on the histological observation, the gonad was categorized into seven phases: immature phase, preripe male phase, ripe male phase, transitional phase, pre-ripe female phase, ripe female phase-I and ripe female phase-II. All the juveniles had ambosexual gonads with testicular and ovarian tissues. Fishes in ripe female phase-II had ovaries with many fully grown yolky oocytes and vitellogenic oocytes, which were absent in ripe female phase-I, and characterized by the presence of many perivitellogenic oocytes and an ovarian cavity but have no testicular tissue. The study confirmed the sex reversal in A. percula from male to female (protandrous hermaphroditism). The field study supported that social structure plays an important role in its sex change.